PERILAKU MENGAKSES SITUS PORNOGRAFI (STUDI FENOMENOLOGI TENTANG PERILAKU REMAJA MENGAKSES SITUS PORNOGRAFI DI PERGURUAN TINGGI MEDAN) - Kiara Aulia Pelawi; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
Phenomenological research on adolescent behavior accessing pornographic sites in Medan universities is an effort to deeply understand the experiences and perceptions of adolescents related to this phenomenon. This study aims to explain how and why adolescents in Medan universities engage in the behavior of accessing pornographic sites In this study, in-depth interviews were conducted with a number of college adolescents who voluntarily expressed their experiences and thoughts regarding the behavior of accessing pornographic sites. The results of this study show that easy access to the internet and the use of digital technology have influenced adolescent behavior in accessing pornographic content. Teens admit that they are tempted to access pornographic sites because of curiosity, social pressure, and loneliness. Some other factors that influence this behavior include lack of supervision from parents or caregivers, lack of understanding of the negative effects of pornography, and lack of healthy entertainment or activity alternatives. However, the study also highlights some of the negative impacts of behavior accessing pornographic sites on adolescents. Some of the impacts identified include changes in perceptions of sexuality, dissatisfaction in interpersonal relationships, unrealisticity in sexual expectations, and decreased self- satisfaction. In addition, teens also reported feelings of guilt and anxiety associated with the activity. In conclusion, this study shows that the behavior of accessing pornographic sites among college teenagers in Medan is a significant phenomenon. It is important to understand the factors that influence this behavior in order to develop effective strategies to overcome this problem. Comprehensive sexual education, better supervision from parents and caregivers, and the development of healthy entertainment alternatives are some of the suggestions that emerged from this study to reduce the behavior of accessing pornographic sites in adolescents.